ANALISIS CORPORATE SOCIAL RESPONSIBILITY TERHADAP CUSTOMER LOYALTY: STUDI KASUS PADA AMDK MEREK AQUA - Fernanda, Redithya Ega; Kholmi, Masiyah (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2025)
This study examines the effect of Corporate Social Responsibility (CSR) on customer loyalty for the AQUA bottled water brand. CSR has become important in modern business, not only to enhance the company's reputation but also to create a positive impact on society and the environment. Through a qualitative descriptive method, this study analyzes various CSR programs implemented by AQUA, such as the WASH (Water Access, Sanitation, and Hygiene) initiative and the AQUA Lestari program, which focuses on providing access to clean water and environmental preservation. The results show that consumers' participation in CSR programs increases their trust and loyalty to the brand. Consumers feel more emotionally connected to AQUA when the company demonstrates commitment to social and environmental issues. The conclusion of this study confirms that the integration of CSR in business strategy is critical to achieving sustainability and long-term growth, as well as strengthening relationships with customers and communities.